MITOS TIKUS DAN MANUSIA TIKUS DALAM THE RAT CATCHER KARYA WES ANDERSON - Rommel Utungga Pasopati; Dian Oktavia; Albert Wijaya Kusuma; Kusuma Wijaya; Muhammad Reza Ishadi Fadillah (Lingue : Jurnal Bahasa, Budaya, dan Sastra, 2025)
This study aims to understand the myth of the rat and the 'Rat Man' through their behavior in the film The Rat Catcher. The research employs a qualitative method with data collection through note-taking. The researcher watches the film and records dialogues related to the research theme. The data analysis technique is conducted by analyzing the dialogues and behaviors in The Rat Catcher1 in relation to the concept of myth within Claude Levi-Strauss's structuralism. Myths are often associated with events in society that influence customs or lifestyles of those who believe in them. Through Levi-Strauss's structuralist analysis, it was found that the failure of the Rat Man to catch the rat highlights the irony of the myth. The various methods he employs to catch the rat, ranging from ordinary to unique and even extreme, yield no results. In conclusion, the Rat Man remains trapped in an illusion that does not prove the myth he believes in, thus the myth about the rat continues to linger in his mind. The contribution of this study is to provide an understanding of how the myths of the rat and the 'Rat Man' can be analyzed through the lens of Claude Levi-Strauss's structuralism to reveal the irony and failure in the application of these myths.